PENGARUH COOPERATIVE LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP HASIL BELAJAR KOGNITIF IPAS SISWA KELAS V - Maulidya, Maulidya; Halidjah, Siti; Kartono, Kartono (Universitas Tanjungpura, 2024)
This research was motivated by the results of teacher interviews which stated that students were less enthusiastic about learning, less active in discussing and had difficulty understanding the material being taught so that cognitive learning outcomes were low, so the cooperative learning model assisted by audiovisual media was chosen as the variable for this research. The research method used was an experiment in the form of a quasi-experimental design, a nonequivalent control group design model. The sample for this research was classes VA and VB at State Elementary School 05 Pontianak City. The sample was determined using the random sampling method. The data collection technique used is a measurement technique. The instrument used is a multiple choice test with 20 questions. Based on the research results and hypothesis test calculations using SPSS, tcount was 3.53 2.04 ttable. This shows that there is an influence of the STAD type cooperative learning model assisted by audiovisual media on the cognitive learning outcomes of science and science subjects for class V students at State Elementary School 05 Pontianak City. The results of the effect size (ES) calculation obtained a value of 2.49 indicating high criteria, so it can be concluded that the STAD type cooperative learning model assisted by audiovisual media has a high influence on the cognitive learning outcomes of class V students at State Elementary School 05 Pontianak City.